Readiness to Change and Prospective Effects of Weight Management Programs in Pediatric Nonalcoholic Fatty Liver Disease - Voytek Slowik; Heather Wasserkrug; Ryan T. Fischer; Mark Connelly; Amanda D. Deacy; Sarah Hampl; James F. Daniel (Wiley, 2021)
Non‐alcoholic fatty liver disease (NAFLD) is an increasing problem in pediatrics with limited treatment options. We prospectively assessed outcomes in patients managed in a hepatology clinic (HC) alone vs. those managed in combination with a multidisciplinary weight management program (MWMP). We describe each group's readiness to change at the time of NAFLD diagnosis. Patients diagnosed with NAFLD were given a modified Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES) at enrollment (T1) to assess readiness to change. They were then followed at 3-9 months (T2) and at 10-15 months (T3). Linear mixed models were used to evaluate changes in body mass index (BMI), BMI z‐score, and transaminases over time and between the two groups. There were no significant treatment group main effects or treatment × time interactions for our primary end points for HC alone (n = 75) or with MWMP (n = 18). There was a significant main effect for time for BMI z‐score, with BMI z‐scores declining on average by 0.0568 (P = 0.004) from visit to visit. Low SOCRATES subscales scores in HC alone (n = 33) or with MWMP (n = 4) suggested a patient population with low recognition of disease and likelihood of taking steps for change. Patients with obesity and NAFLD had low scores on all three SOCRATES subscales. Despite this, both groups had improvement in BMI z‐score without significant difference between the two treatment groups in other primary end points. Further study is needed to identify the most effective patient selection and treatment strategies for pediatric patients with NAFLD, including pharmacotherapy and surgery.